Exploring language styles of teacher and students' verbal interaction - Rachmat Rachmat (Center for Humanities and Innovation Studies, 2022)
This research aims to find out the teacher in the classroom uses the verbal interaction between students and teacher, and language styles. The research was conducted at one of the Islamic Boarding High Schools in Maros regency, South Sulawesi, Indonesia. This research used a descriptive qualitative method, and the data was collected using observation and interviews of the teaching and process in the classroom. The results of this study demonstrated that verbal interaction and language style in a classroom are functioning effectively because the instructor can manage the situation and make the situation function properly by asking largely students for feedback. Nine types were explained in the findings: intrapersonal interaction, intrapersonal interaction, small group interaction, public interaction, formal style, informal style, group project, peer instruction, and discussion or debates. Based on the result above, it could be concluded that the verbal interaction between students and teacher and language styles in the classroom was running well.